2013
DOI: 10.1038/ajg.2013.336
|View full text |Cite
|
Sign up to set email alerts
|

Opium Use and Risk of Mortality from Digestive Diseases: A Prospective Cohort Study

Abstract: Background Opium use, particularly in low doses, is a common practice among adults in northeastern Iran. We aimed to investigate the association between opium use and subsequent mortality from disorders of the digestive tract. Methods We used data from the Golestan Cohort Study (GCS), a prospective cohort study in northeastern Iran, with detailed, validated data on opium use and several other exposures. A total of 50,045 adults were enrolled during a four-year period (2004–2008) and followed annually until D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…In the latter study, high-temperature cooking methods, including barbecuing and frying, were also found to increase the risk for oesophageal cancer. In Iran, opium use has been found to increase mortality from oesophageal cancer by 50% 26. Also, low socioeconomic status, poverty and poor oral hygiene have been linked to an increased risk of oesophageal SCC 23 27 28.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, high-temperature cooking methods, including barbecuing and frying, were also found to increase the risk for oesophageal cancer. In Iran, opium use has been found to increase mortality from oesophageal cancer by 50% 26. Also, low socioeconomic status, poverty and poor oral hygiene have been linked to an increased risk of oesophageal SCC 23 27 28.…”
Section: Discussionmentioning
confidence: 99%
“…Among these risk factors are poor oral hygiene and tooth loss (37, 113, 114), opium use (36, 115-117), infection with Ebstein-Barr virus (118, 119), and eating pickled vegetables (120). …”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 99%
“…In the West, there is an epidemic of opioid prescribing,3 4 which in USA has led the surgeon general to discourage strongly the prescription of these drugs for non-malignant pain in adults 5. As well as the risk of long-term addiction and higher rates of death among opioid users,6 these drugs have undesired actions on the GI tract, due to the location of µ-opioid receptors. Opioids lead to delayed GI transit and hard, infrequent stools,7 with up to 50% of individuals taking these drugs reporting constipation, which they attribute to opioid use 8 9…”
Section: Introductionmentioning
confidence: 99%